2003
DOI: 10.1081/iph-120024500
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytokine Synthesis of Leukocytes by a β‐Glucan Preparation, SCG, Extracted from a Medicinal Mushroom,Sparassis crispa

Abstract: Sparassis crispa is edible mushroom recently cultivable in Japan. It contains significantly high content (approximately 40%) of 6-branched 1,3-beta-D-glucan showing antitumor activity in mice. We recently purified a beta-glucan preparation designated as "SCG." It was considered worth while to test SCG in vitro with whole blood collected from human volunteers. The present study is focusing on the cytokine productivity of SCG in an in vitro human system. The following results were observed: (i) SCG dose dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…routes over a wide range of concentrations [15,16], and the effect was augmented by combination with isoflavone aglycone [17]. SCG stimulated leukocytes to produce cytokines in preparations of human peripheral blood mononuclear cells [18] and splenocytes from mice [19]. These results show that SCG could enhance immune responses in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 72%
“…routes over a wide range of concentrations [15,16], and the effect was augmented by combination with isoflavone aglycone [17]. SCG stimulated leukocytes to produce cytokines in preparations of human peripheral blood mononuclear cells [18] and splenocytes from mice [19]. These results show that SCG could enhance immune responses in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 72%
“…Very few reports have suggested that this mushroom exhibits antitumor and antiallergic activities (Ohno et al, 2000;Yamamoto et al, 2009) and its major principles are identified as polysaccharide fractions composed of a backbone of β-(1→3)-linked D-glucopyranosyl residues with β-D-glucopyranosyl groups joined through O-6 and O-2 of D-glucose (Tada et al, 2007;Park et al, 2009). Interleukin (IL)-8, GM-CSF and interferon (IFN)-γ are reported to be produced by Sparassis crispa β-glucan (Harada et al, 2002;Nameda et al, 2003;Harada and Ohno, 2008). In addition, this mushroom has been also reported to contain some chemical constituents such as sequiterpenoids and benzoate derivatives that possess antifungal and antibacterial activities (Harada et al, 2005;Kodani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As its mechanism of action, sparan increased cytokine production by human peripheral blood mononuclear cells (PBMCs) [8] and mouse spleen cells [5,9,10]. Sparan directly induced adherent cells to produce TNF-α and IL-12, whereas cell-cell contact between adherent cells and CD4+ T cells was required for the induction of IFN-γ and GM-CSF by sparan [11].…”
Section: Introductionmentioning
confidence: 99%